LIFELONG EDUCATION RELATED ISSUES OF DANCE GROUP LEADERS WITHIN THE AMATEUR MOVEMENT IN LATVIA - Spalva, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
As a country with a relatively small population (approximately 2 million), Latvia can take pride in the number of people who are practicing folk dance at amateur level. Based on 2015 information provided by the Latvian National Centre for Culture, this amateur movement counts 603 dance groups (over 12 000 dancers) and accordingly 417 dance group leaders. The main goal of dance group activities is to sustain the idea of national consciousness through the means of folk dance, which is a meaningful factor in the strengthening of national identity to progress to a modern and national country. The National Song and Dance Festival, which takes place every five years in Latvia and which is one of the UNESCO Masterpieces of Oral and Intangible Heritage of Humanity, is a significant tool for maintaining a national cultural environment within amateur dance. The festival combines artistic, national social and other functions of significance to social development.All above-mentioned conditions determined the research problem – how to develop dance group leader lifelong education programmes more successfully, in order for these to purposefully integrate participants of various levels of professionalism. The research aim is to analyse existing lifelong education contents available to dance group leaders, along with the challenges and risks they pose. The study predominantly makes use of empirical methods – lifelong education programme participant surveys and their analysis; analysis of the artistic performance of dance groups.